Medial Quadriceps Tendon-Femoral Ligament Reconstruction: A Technique Description and Short-Term Outcomes. Issue 2 (June 2021) - Bowman, Eric N.; Hallock, Justin D.; Wells, Daniel B.; El Masri, Ahmad O.; Phillips, Barry B.
Abstract : Purpose: The medial quadriceps tendon-femoral ligament (MQTFL) is a distinct structure extending from the distal adductor tubercle to quadriceps tendon and provides medial support. Anatomic reconstruction is an alternative to transosseous medial patellofemoral ligament reconstruction for recurrent patellar instability that eliminates concern for patellar fracture. The purpose of this study is to describe a modified surgical technique for the treatment of patellar instability and evaluate short-term outcomes. Methods: Modified MQTFL reconstructions were performed between April 2012 and November 2015 for persistent patellar instability for which nonoperative treatment had failed. Included patients had >2+ quadrants of laxity and history of recurrent patellar dislocation. Patients with concurrent injuries, Dejour C or D trochlear dysplasia, or who required a realignment osteotomy were excluded. Anatomic reconstruction of the MQTFL was performed utilizing a sling in the distal medial quadriceps tendon and doubling the graft back to the femoral isometric point. Clinical outcomes were documented via a telephone survey. Physical examination findings were obtained by chart review at 3 to 6 months postoperative. Results: Thirteen modified MQTFL reconstructions were evaluated with a mean follow-up of 29 months. At follow-up, all patients had achieved a full range of motion and 1 to 2 quadrants of passive lateral glide with a good endpoint. There were no recurrent dislocations or complications directly related to the surgery. Overall satisfaction rate was 98%. Median Tegner preinjury and postoperative were 7; 67% returned to sports at the same level. Mean Lysholm and Kujala scores were 97 (SD=4). Conclusion: Modified MQTFL reconstruction is a safe and effective procedure for the treatment of patellar instability. This procedure is a valuable technique for avoiding potential patellar fracture associated with transosseous medial patellofemoral ligament fixation. Level of Evidence: Level IV—case series.